The information-giving skills of resident physicians: relationships with confidence and simulated patient satisfaction - Ishikawa, Hirono (BMC Med Educ, 2017)
BACKGROUND: Sharing information is crucial for discussion of problems and treatment decision making by patients and physicians. However, the focus of communication skills training in undergraduate medical education has been on building the relationship and gathering information; thus, resident physicians tend to be less confident about sharing information and planning treatment. This study evaluated the medical interviews conducted by resident physicians with a focus on information giving, and investigated its relationships with their confidence in communication and simulated patient (SP) satisfaction. METHODS: Among 137 junior resident physicians at a university hospital in Japan who participated in a survey of communication skills, 25 volunteered to conduct simulated medical interviews. The medical interviews were video-recorded and analyzed using the Roter Interaction Analysis System, together with additional coding to explore specific features of information giving. The SPs evaluated their satisfaction with the medical interview. RESULTS: Resident physicians who were more confident in their communication skills provided more information to the patients, while SP satisfaction was associated only with patient-prompted information giving. SPs were more satisfied when the physicians explained the rationales for their opinions and recommendations. CONCLUSION: Our findings underscore the importance of providing relevant information in response to the patient requests, and explaining the rationales for the opinions and recommendations. Further investigation is needed to clinically confirm our findings and develop an appropriate communication skills training program.